2012
DOI: 10.1063/1.4731711
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of drift waves in a linear magnetized plasma column

Abstract: In magnetically confined fusion plasmas, drift wave driven turbulence can lead to enhanced particle transport from the plasma. Because of this, a significant research emphasis has been placed on the suppression of drift waves in the plasma edge. However, the combination of the toroidal geometry and short plasma lifetimes can make it difficult to fully characterize the properties of these instabilities. Because linear magnetized plasma devices offer a combination of simpler geometry and steady state plasma gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Linear devices such as LAPD, which are very long with relatively low magnetic field, observe saturated turbulence as expected [13]. Experimental evidence has shown that drift-waves can be suppressed in the presence of an external potential bias imposing a radial electric field on the plasma [14]; however, a comprehensive scan of magnetic field and device length has not to our knowledge been conducted. This work therefore serves as a theoretical prediction of the plasma behaviour in regards to resistive drift-wave turbulence stability in linear devices.…”
Section: Discussionmentioning
confidence: 94%
“…Linear devices such as LAPD, which are very long with relatively low magnetic field, observe saturated turbulence as expected [13]. Experimental evidence has shown that drift-waves can be suppressed in the presence of an external potential bias imposing a radial electric field on the plasma [14]; however, a comprehensive scan of magnetic field and device length has not to our knowledge been conducted. This work therefore serves as a theoretical prediction of the plasma behaviour in regards to resistive drift-wave turbulence stability in linear devices.…”
Section: Discussionmentioning
confidence: 94%
“…The density gradient is negligible compared to the electric field, ruling out the possibility that the low‐frequency mode is a drift wave. In addition, drift waves are stabilized by velocity shear [ Gavrishchaka et al ., ; DuBois et al ., ].…”
Section: Resultsmentioning
confidence: 99%